Effect of Nonviral Factors on Hepatitis C Recurrence After Liver Transplantation - Cameron, Andrew M. (2006)
OBJECTIVE: Hepatitis C (HCV) is now the most common indication for orthotopic liver transplantation (OLT). While graft reinfection remains universal, progression to graft cirrhosis is highly variable. This study examined donor, recipient, and operative variables to identify factors that affect recurrence of HCV post-OLT to facilitate graft-recipient matching. METHODS: Retrospective review of 307 patients who underwent OLT for HCV over a 10-year period at our center. Recurrence of HCV was identified by the presence of biochemical graft dysfunction and concurrent liver biopsy showing diagnostic pathologic features. Time to recurrence was the endpoint for statistical analysis. Five donor, 6 recipient, and 2 operative variables that may affect recurrence were analyzed by univariate comparison and Cox proportional hazard regression models. RESULTS: Recurrence-free survival in the 307 study patients was 69% and 34% at 1 and 5 years, respectively. Four predictive variables related to either donor or recipient characteristics were identified. Advanced donor age, prolonged donor hospitalization, increasing recipient age, and elevated recipient MELD scores were found to increase the relative risk of HCV recurrence. Examination of HLA disparity between donors and recipients demonstrated no correlation between class I or class II mismatches and recurrence-free survival. CONCLUSIONS: We have identified donor and recipient characteristics that significantly predict hepatitis C recurrence following liver transplantation. These factors are identifiable before transplant and, if considered when matching donors to HCV recipients, may decrease the incidence of HCV recurrence after OLT. A change in the current national liver allocation system would be needed to realize the full value of this benefit.